Historical time in Secondary Education: An Analysis of the Conceptual and Methodological Notions of Teachers from the San José Norte Region, during 2021 and 2022 - Naranjo Segura, Juan Carlos (2023)
This article points out the results of an investigation in which the conceptual and methodological notions about historical time were described and analyzed by the Social Studies teachers of the San José Norte Regional Office, and their relationship with the development of skills in the students, during 2021 and 2022, through a mixed methodology. A questionnaire was applied to 58 teachers where the conceptual domain of twenty-one concepts linked to historical time was identified. In order to investigate the methodological notions, a qualitative questionnaire was applied to twelve teachers and three semi-structured interviews, information that was compared with the observations of their lessons. The main results of the research were: 89.2% of the teachers participating in the research demonstrated an intermediate command of the concepts linked to historical time. On the other hand, a contrast was found between the discourse of the teachers, where they showed a mastery of methodological notions, with the lessons. In the latter, less clarity and a deficient knowledge of the methodology were observed, predominantly a didactics from a content transmission perspective and oriented to a great extent to memorization and repetition. The main conclusion was that the conceptual and methodological mastery levels presented by teachers are not enough to determine if it is possible to achieve the development of skills linked to historical time in the group of students.